The March 2021 Italian constitutional court ruling on surrogacy: a prelude to common European legislation for the sake of reproductive health?. (2nd January 2022) - Zaami, Simona; Del Rio, Alessandro; Negro, Francesca; Varone, Maria Cristina; Marinelli, Susanna; Montanari Vergallo, Gianluca
Abstract: Purpose: Surrogacy is an arrangement by which a surrogate mother bears a child for another couple or person, and is often thought of as a form of 'treatment' for couples (or even individuals) with fertility or sterility issues. Still, surrogacy entails ethical issues related to gender, fundamental human rights, exploitation and inequality. Materials and methods: Starting from the Italian state of affairs, the authors have set out to briefly expound upon such complexities, taking into account relevant jurisprudence on the subject, with a particular focus on inter-country surrogacy and second-parent adoption, which can themselves engender significant legal dilemmas. When residents of countries where surrogacy is banned travel abroad and hire a surrogate, that may lead to considerable legal hurdles as well. Results: In Italy and elsewhere, the courts have all too often had to fill the vacuum left by the lack of targeted legislation. The Italian Constitutional Court has recently urged lawmakers to enact new legislation to uphold the minor's best interests. In fact, while some countries recognise the surrogate as the legal parent, others ascribe parenthood to the commissioning parents. That discrepancy can lead to a 'clash of laws', resulting in children ending up stateless and unable to maintain an already established family relationship. Conclusions: Just like fundamental protection of human rights and public health, the regulation of revolutionary technologies that change the very notion of reproduction, parenthood, and human identity needs to be governed by uniform standards, shared at least by nations which espouse common core values.